Covert cows and Chick-fil-A : how faith, cows, and chicken built an iconic brand - Robinson, Steve, 1950- (Thomas Nelson, 2019)
"The longtime chief marketing officer for Chick-fil-A tells the inside story of how the company turned prevailing theories of fast-food marketing upside down and built one of the most successful and beloved brands in America. During his thirty-four-year tenure at Chick-fil-A, Steve Robinson was integrally involved in the company's growth--from 184 stores and $100 million in annual sales in 1981 to over 2,100 stores and over $6.8 billion in annual sales in 2015--and was a first-hand witness to its evolution as an indelible global brand. In Covert Cows and Chick-fil-A, Robinson shares behind-the-scenes accounts of key moments, including the creation of the Chick-fil-A corporate purpose and the formation and management of the now-iconic "Eat Mor Chikin" cow campaign. Drawing on his personal interactions with the gifted team of company leaders, restaurant operators, and the company's founder, Truett Cathy, Robinson explains the important traits that built the company's culture and sustained it through recession and many other challenges. He also reveals how every aspect of the company's approach reflects an unwavering dedication to Christian values and to the individual customer experience. Written with disarming candor and revealing storytelling, Covert Cows and Chick-fil-A is the never-before-told story of a great American success."--